Black hole mass and spin measurements through the relativistic precession model: XTE J1859+226. Issue 1 (4th October 2022) - Motta, S E; Belloni, T; Stella, L; Pappas, G; Casares, J; Muñoz-Darias, A T; Torres, M A P; Yanes-Rizo, I V
ABSTRACT: The X-ray light curves of accreting black holes and neutron stars in binary systems show various types of quasi-periodic oscillations (QPOs), the origin of which is still debated. The relativistic precession model identifies the QPO frequencies with fundamental time-scales from General Relativity, and has been proposed as a possible explanation of certain types of such oscillations. Under specific conditions (i.e. the detection of a particular QPOs triplet) such a model can be used to obtain self-consistent measurements of the mass and spin of the compact object. So far this has been possible only in the black hole binary GRO J1655-40. In the RXTE/PCA data from the 1999–2000 outburst of the black hole transient XTE J1859+226 we found a QPO triplet, and used the relativistic precession model to obtain high-precision measurements of the black hole mass and spin – M = (7.85 ± 0.46) M⊙, a * = 0.149 ± 0.005 – the former being consistent with the most recent dynamical mass determination from optical measurements. Similarly to what has been already observed in other black hole systems, the frequencies of the QPOs and broad-band noise components match the general relativistic frequencies of particle motion close to the compact object predicted by the model. Our findings confirm previous results and further support the validity of the relativistic precession model, which is the only electromagnetic-measurement-based method that so far has consistently yielded spins close to those from the gravitational waves produced by merging binary black holes.